Melioidotic Otomastoiditis in Triplets: A Rare Pediatric Cluster with Intracranial Complications - Chayanit Kritpracha; Viraporn Atchariyasathian; Pittayapon Pitathawatchai (Journal of Health Science and Medical Research, 2026)
Melioidosis, caused by Burkholderia pseudomallei (B. pseudomallei), is endemic in tropical regions, including Thailand. Often called “the great mimicker,” it can involve multiple organ systems and present with varied clinical manifestations. While the lungs are the most commonly affected site, head and neck manifestations occur in 14.0–25.0% of cases, primarily as neck abscesses or suppurative parotitis, and otologic involvement is exceedingly rare. We report a cluster of melioidotic otitis media in three 15-month-old triplets, two of whom developed intracranial complications requiring surgical intervention. All patients presented with bilateral otitis media, and melioidosis was confirmed through culture or serologic titer. The two patients with intracranial involvement underwent surgical management and received prolonged treatment with meropenem followed by oral trimethoprim-sulfamethoxazole. At the 7-month follow-up, both surgically treated patients demonstrated complete recovery without chronic sequelae. This case series highlights the importance of considering B. pseudomallei infection in refractory otitis media in endemic settings and underscores the need for early recognition of potentially life-threatening intracranial complications.